2009
DOI: 10.1016/j.compscitech.2008.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Mode III interlaminar fracture of carbon/epoxy laminates using the edge crack torsion (ECT) test

Abstract: The mode III interlaminar fracture of carbon/epoxy laminates was evaluated with the edge crack torsion (ECT) test. Three-dimensional finite element analyses were performed in order to select two specimen geometries and an experimental data reduction scheme. Test results showed considerable non-linearity before the maximum load point and a significant R-curve effect. These features prevented an accurate definition of the initiation point. Nevertheless, analyses of non-linearity zones showed two likely initiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 25 publications
5
44
0
Order By: Relevance
“…Extensive work on Mode I and Mode II fracture is reported in the literature, but less work has been reported on Mode III despite its importance in edge delamination [20,21]. Donaldson [22] has reported that split cantilever beam (SCB) tests can be used to measure the Mode III fracture energy G IIIC .…”
Section: Mode III Interlaminar Fracture Toughness Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive work on Mode I and Mode II fracture is reported in the literature, but less work has been reported on Mode III despite its importance in edge delamination [20,21]. Donaldson [22] has reported that split cantilever beam (SCB) tests can be used to measure the Mode III fracture energy G IIIC .…”
Section: Mode III Interlaminar Fracture Toughness Testingmentioning
confidence: 99%
“…The Mode III fracture toughness is calculated by Irwin-Kies relation [7,20] CLT torsional shear moduli of the uncracked and cracked parts of the specimen, respectively, derived by Lee [25].…”
Section: Mode III Interlaminar Fracture Toughness Testingmentioning
confidence: 99%
“…The experimental work was carried out on the epoxy resin reinforced by the E-glass unidirectional and woven fiber with the density of 1.46 g/cm 3 , 500 g/m 2 and 303 g/m 2 , respectively. The laminates were provided by hand lay-up with compression molding.…”
Section: Materials and Specimens Preparationmentioning
confidence: 99%
“…Delamination is an insidious failure mode that is frequently present within the composite and it may easily escape detection [3]. Passive methods, such as AE, may improve the reliability and confidence of delamination detection [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Mode II component can be reduced to a reasonable level with an appropriate choice of the specimen geometry [18e20,22]. It is not satisfactory to apply the data reduction schema based on experimental CC method for determining G IIIC because a large number of specimens with different initial crack lengths had to be used, and the value of G IIIC was found to increase with the crack length [22]. Moreover, small initial crack lengths for ECT specimens should be preferable for measuring G IIIC [26], but too small initial crack lengths would decrease the accuracy because of the uncertainty in the real crack length measurement.…”
Section: Introductionmentioning
confidence: 99%